Biology and harmfulness of Planococcus vovae (Nassonov) (Hemiptera: Pseudococcidae) in Belgrade area (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Planococcus vovae (Nassonov) (Hemiptera: Pseudococcidae) is an important pest on plants of the family Cupressaceae. Its numerous populations have been present in recent years on Juniperus spp. in Belgrade. Feeding by sap-sucking on all aboveground plant organs, it causes growth stagnation, chlorosis, drying of needles and branches, and even of entire plants under heavy infestation. Additionally, the scale excretes large quantities of honeydew, on which sooty mold develops, reducing photosynthesis and causing faster plant deterioration.Throughout 2007 and 2008, P. vovae was recorded on Juniperus spp. in 12 localities inBelgrade, and on Thuja sp. in a single locality. The pest was found to develop three generations per year and overwinter on branches at the egg or second instar stages. The first generation adults were observed at the end of May, the second generation at the beginning of August, while the third generation was recorded at the beginning of October. Different overwintering modes, and variable oviposition, embryonic and larval development periods led to an overlapping of generations and continuous presence of all developmental stages on plants.In different localities the infestation of plants varied in abundance from a few individualspecimens to very large colonies. The highest infestation intensity was recorded in thelocalities Bežanija, Dorćol and Voždovac.The predatory species Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) andNephus bipunctatus (Kugelann) (Coleoptera: Coccinelidae) were found in the scale colonies. Regarding N. bipunctatus, this was its first record as a new species in the Serbian fauna.
Keywords: Planococcus vovae; Scales; Infestation; Hemiptera